Polish Noble Devils. Historical Aspect - Stolarczyk, Tomasz (Diabeł Boruta w dawnej kulturze polskiej, 2021)
This article presents noble devils, also known as robes. They were Polish nobles, who were considered incarnated devils for their actions, while still alive. After death, in the popular opinion they turned into demonic and devilish figures. They mainly included cruelty, bullying other people, including their subjects and even family members, dangerous robbers, assaulting, imprisoning and even killing other people for money and treasures, adventurers committing rapes and even murders. Among the Polish noble devils there were also people considered traitors to the Nation, and among them the man who first used the infamous liberum veto. On the other hand, one of the noble devils was the semi-legendary Boruta, probably a noble from Łęczyca, endowed with exceptional strength and considered a good devil.